UPAYA TENAGA PENDIDIK DALAM MENINGKATKAN MOTIVASU PESERTA DIDIK DALAM MENGHAFAL AL-QUR’AN - Dina Azizah; Ilham Adbullah; Parlan Parlan (UNIB Press, Universitas Bengkulu, 2019)
The purpose of this research in general is to described about how students motivation in memorization al-quran at Bakti Ilaahi Tahfidz House bengkulu city. Methods used in this study was a qualitative methodology a data collection, using a technique interview observation and documentation. Based on the research the conclusions may be drawn that first, santri motivation in memorization quran varies and tending to less stable, this is santri age young 12-15 need assistance and the year guidance so reminded santri tight to individual motivation can so stable and the purpose of learning can be achieved easily. Second, educators have tried to in full to increase the motivation is to submit those, a gift, competition, knowing the outcome, a compliment, punishment and attract. But we cannot deny that the motivation to learn consists of two which is intrinsic motivation or intrinsic and motivation from the outside namely, extrinsic motivation intrinsic motivation is much better than the extrinsic motivation because intrinsic motivation comes from individuals santri alone or awareness of the students own. Third, factors that give rise to motivate students is a factor intrinsic and extrinsic but more dominant derived from extrinsic factor at the sight of motivation santri unstable santri will cheer on when given the recognition and punishment by educators and motivation santri will increase third educators provides guidance motivation that contains about memorizing the quran and fishing for the growing intrinsic motivation in himself students.. Keywords :Motivation, Students, Memorizing the Al-quran, Tahfidz House